Improving well-being through better housing policy in New Zealand - Barker, Andrew (OECD Economics Department Working Papers, 2019)
New Zealand's housing supply has not kept pace with rising demand, including from net immigration. Affordability has worsened, particularly for low-income renters. Government action is underway to allow new housing through initiatives such as the Urban Growth Agenda, KiwiBuild and the Housing and Urban Development Authority, but further steps are needed to improve well-being. Clear overarching principles for sustainable urban development and rationalisation of strict regulatory containment policies would allow the planning system to better respond to demand for land. Incentives for local governments to accommodate growth could be increased by giving them access to additional revenue linked to local development. More user charging and targeted rates would also help to fund infrastructure required to service new housing. Government delivery of affordable housing through KiwiBuild should be re-focused towards enabling the supply of land to developers, supporting development of affordable rental housing and further expanding social housing in areas facing shortages